ANALISIS PERLAKUAN AKUNTANSI AKTIVA TETAP DAN PENYAJIANNYA PADA LAPORAN KEUANGAN PT HAKA UTAMA SEJAHTERA SAMPANG - Putri, Devi Lestari Pramita; Khotijah, Nur (Fakultas Ekonomi, Program Studi Akuntansi, 2017)
PT Haka Utama Sejahtera Sampang is one of the companies engaged in building construction services. The purpose of this study is to analyze the suitability of accounting treatment of existing assets with accounting treatment of fixed assets according to PSAK number 16, especially regarding the acquisition price of fixed assets and depreciation of fixed assets. This research is a descriptive research. Data collection techniques use interview techniques and documentation techniques. The results of this study say that the accounting treatment of fixed assets, especially regarding Acquisition Price of this company’s fixed assets is not in accordance with PSAK No. 16 because the acquisition price is recorded at the price stated on the purchase note without adding the expenses incurred to obtain the asset and for depreciation of fixed assets of object is not in accordance with PSAK No. 16 because the company does not record the depreciation of fixed assets so that it can not know the depreciated amount of each fixed assets owned by the company. For presentation in the financial statements, the company only records the financial statements of project activities and does not make general financial statements so that the fixed assets are not listed in the project activity report.